Myocardial protection in cardiac surgery: a comprehensive review of current therapies and future cardioprotective strategies - Chiari, Pascal; Fellahi, Jean-Luc (Frontiers in Medicine, 2024)
Cardiac surgery with cardiopulmonary bypass results in global myocardial ischemia–reperfusion injury, leading to significant postoperative morbidity and mortality. Although cardioplegia is the cornerstone of intraoperative cardioprotection, a number of additional strategies have been identified. The concept of preconditioning and postconditioning, despite its limited direct clinical application, provided an essential contribution to the understanding of myocardial injury and organ protection. Therefore, physicians can use different tools to limit perioperative myocardial injury. These include the choice of anesthetic agents, remote ischemic preconditioning, tight glycemic control, optimization of respiratory parameters during the aortic unclamping phase to limit reperfusion injury, appropriate choice of monitoring to optimize hemodynamic parameters and limit perioperative use of catecholamines, and early reintroduction of cardioprotective agents in the postoperative period. Appropriate management before, during, and after cardiopulmonary bypass will help to decrease myocardial damage. This review aimed to highlight the current advancements in cardioprotection and their potential applications during cardiac surgery.